Development of Numerical Logic Textbook Containing Characters through Elementary School Students’ Thinking Analysis - Wijayanti, Lina (International Conference on Elementary Education, 2020)
This study aims to develop a numerical logic textbook through elementary school students' thinking analysis and containing character education. Numerical Logic is one of the required competencies in mathematics that must be mastered by the pre-service teacher of elementary school. This subject is intended to see various points of view of students in the process and solving mathematical problems. Nowadays no teaching material model explains the numerical logic of elementary school students, so in the end, the teacher will teach mathematics according to the teachers’ point of view. Besides, they are required to be good role models for their students with character education. This study used the 4D Model where consist of four stages, namely define, design, develop, and disseminate. Method of collecting and analyzing data used was documentation method to get textbook data and observation to analyze elementary students’ thinking data before textbooks developed, the questionnaire to get expert validation data and readability by the students of the pre-service teacher of elementary school as well as a test to obtain data on the eligibility of test instrument. The validation results show that the textbook is feasible to use even though there are some improvements however not change the concept. The readability test result shows that some words need to be revised. It can be concluded that the textbook is effective and readable to be used in a class